La senilità e la cura: Da mani mortali (2012) di Biancamaria Frabotta - Stroppa, Sabrina (L'ospite ingrato, 2024)
The essay offers a reading of Biancamaria Frabotta’s book of senility, Da mani mortali (2012), in which the author has to come to terms with the time that remains, while shrinks the «physical and mental space» of what Frabotta herself called viandanza. The loneliness of old age is accompanied by the ‘phantasmata’ of the poets, who, although they know that mortal life is destined not to be reborn, adhere to the work of hands: whether poems or flowers, mortal hands shape what remains and resists. Caring for what is there, in the present, or what is destined to remain, in the long future devoid of the self, is therefore the only possible perspective, the only form of survival. The essay also follows the constitution of the final collection, starting with the various plaquettes of which it is composed: Frabotta sews, modifies and adapts the pre-existing poems, to give them the form of a book. The final arrangement brings out a secret mournful undercurrent, which finds Homeric accents in addressing the theme of death, and the disappearance of close friends.